What might be a better way to target new special drawing rights to struggling economies? - Southern and Eastern Africa Trade Information and Negotiations Institute (SEATINI) Uganda (Southern and Eastern Africa Trade Information and Negotiations Institute (SEATINI) Uganda, 2021)
The Global pandemic has resulted in a multitude of crises affecting Low Income Countries (LICs). LICs in general are witnessing fiscal challenges in form of shrinking revenue collections, and burdensome debt repayments. Many of these countries are in the midst of a debt crisis that has been accelerated by the COVID-19 pandemic. They are now having to borrow more to finance economic recovery and also to secure vaccines. It remains worth noting that borrowing will increase public debt and present further a debt sustainability challenge. In 2020 majority of Sub Saharan African countries secured loans from the IMF and the African Development Bank for the COVID-19 response and this will push public debt levels close to 100 percent1 of Gross Domestic Product (GDP) sooner.